PENERAPAN SISTEM OUTSOURCING DI PERUSAHAAN SWASTA DALAM PERSPEKTIF PERLINDUNGAN HUKUM HAK-HAK PEKERJA KONTRAK - Purwanidjati, Sri Rahayu (Wacana Hukum, 2011)
Abstracts : Outsourcing is a transfer or certain job from a company to a third party on  which held by purpose to divide the risk and lessen the company's burden. Such job transfer is held on the base of operational cooperative agreement between the outsourcing principal and the outsource executive companies. In the practice, the principal company determine the job qualification and condition, and on such base, the outsourcing company recruit prospective employees. In the Acts No. 13 Year of 2003, the regulation on outsourcing is explicitly mentioned that the served sectors are not related with the core bisnis such security guards, cleaning service and so on. Keywords : Outsourcing system, Contract Employee Rights Protection